ORGANIZATION OF PHYSICAL EDUCATION IN THE BLENDED LEARNING - Sosunovsky, V.S.; Radaeva, S.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a model for the organization of physical culture and sports in the process of blended learning. Results and conclusions. The purpose of the model is to provide accessibility and increase the level of students' motivation for physical activity. The developed model is based on such conceptual approaches of pedagogical activity as synergetic, person-centered and systemic. The article provides a theoretical substantiation of the application of these approaches in the process of physical education of various groups of students, and also presents the organizational, meaningful, motivational and productive components of the model. The results of the implementation of the developed model are presented by subject results (knowledge of the role of physical culture and sports in modern society; the ability to use the self-control method to determine the level of health and physical fitness; maintain the proper level of physical fitness by regularly doing physical exercises), personal results (sustained interest and positive attitude to motor activities), meta-subject results (the ability to use the acquired knowledge and formed motor skills to ensure full-fledged social and professional activities).